The determination of heavy metals in coal ash - Susie, Sanjan (Universiti Malaysia Sarawak, UNIMAS, 2008)
Heavy metal is chemical element that cannot be destroyed. Coal is one of the sources used to generate energy and electricity. A coal fired power plant is an energy conversion center that burns fossil fuels to produce electricity. The combustion of coal will produce residue known as ash. The large amount of ashes production will cause the contamination of the environment. This study was carried out to determine the heavy metals in coal ash by using Flame Atomic Absorption Spectrophotometer (FAAS) instrument. The coal ash samples were collected from eight location of coal ash ponds at Sejingkat Power Corporation Sdn Bhd located at the sejingkat. The concentration of heavy metals such as Pb, Zn, Ni, Cd and Mn were analyzed quantitatively. The highest concentration of heavy metal founds in all location of coal ash pond was Pb, followed by Zn, Ni and Cd in descending order. Therefore, Mn shows the lowest concentration.